Prevention of medication errors in healthcare transition of patients treated with apomorphine - M. Ucha Sanmartin; A. Martín Vila; C. López Vidal; M. Caaamaño Barreiro; G. Piñeiro Corrales (Elsevier, 2014)
The transition of patients between different levels of careprocess is a particular risk in the production of medicationerrors. The aim of this paper is to analyze the role of the pharmacistin preventing errors transition care to ensure a safe andcross pharmacotherapy of patients.Transversal, observational and descriptive study in a UniversityHospital that has a pharmacy service that integrates specializedinpatient care and health centers. Transition of care a patienttreated with Apormorfina was analyzed to determine the keypoints of action of the pharmacist. Demographics, disease andmedication history, and care transition episodes were collectedthrough the pharmacy programvand electronics history.The pharmacist did tasks adapting, reconciliation, managementand reporting of medication to the health care team to preventmedication errors in care transition of patients treated withdrugs requiring special handling .In conclusion, this work represents perfectly the key role of thepharmacist as coordinator of safe and transverse pharmacotherapyof patients.